Health-related internet support groups and dental anxiety: The fearful patient's online journey - Buchanan, Heather; Coulson, Neil S.; Malik, Sumaira (International Journal of Web Based Communities, 2010)
Dental fear and anxiety is a common problem affecting many individuals but for some the problem is more severe. This study examined the discussions which took place between members of a dental anxiety/phobia internet support group. A total of 621 messages were thematically analysed and yielded seven key themes which reflected the various points in the 'journey' towards overcoming their fear: a 'I can still remember' b 'I was ashamed to smile or laugh' c 'This big dark secret I can't share with anyone' d 'I can't stand it anymore' e 'I cross the street rather than walk past the dental surgery' f 'Talking to a computer is much easier' g 'Find a dentist that you are comfortable with'. Future research should seek to explore in more depth the nature of the changes in levels of dental anxiety/phobia which might occur as a result of engagement with the group. Copyright © 2010 Inderscience Enterprises Ltd.